3D flower-like ceria silver co-doped zinc oxide catalyst assembled by nanorod for electrochemical sensing of zearalenone in food samples. (1st August 2023) - Manjula, Natesan; Pulikkutty, Subramaniyan; Chen, Shen-Ming
Graphical abstract: Highlights: Ceria silver co-doped zinc oxide composite was synthesized. The prepared material shows good sensor performance for zearalenone detection. The low detection limit of 0.26 µg/mL was achieved. The sensor showed good recovery with food samples. Abstract: To ensure food safety and quality, the development of rapid detection of mycotoxins using sensitive and accurate methods is essential. Zearalenone is one of the mycotoxins found in cereals, and its toxicity poses a serious risk to humans. For this concern, a simple ceria silver co doped zinc oxide (Ce-Ag/ZnO) catalyst was prepared by coprecipitation approach. The physical properties of the catalyst were characterized by XRD, FTIR, XPS, FESEM, and TEM. The Ce-Ag/ZnO catalyst was used as an electrode material for the detection of ZEN in food samples due to its synergistic effect and high catalytic activity. The sensor exhibits good catalytic performance with a detection limit of 0.26 µg/mL. Moreover, the efficiency of the prepared sensor was confirmed by selectivity in interference studies and real-time analysis in food samples. Our research is an essential technique for using trimetallic heterostructures to study the construction of sensors.